STRATEGI PENGEMBANGAN USAHATANI KOPI ARABIKA DI KECAMATAN RONGGUR NIHUTA KABUPATEN SAMOSIR - Ginting, Albina; Nainggolan, Hotden; Situmorang, Nolima; Situmorang, Echa; Simanjuntak, Trinitatis (Universitas Medan Area, 2024)
Samosir Regency is one of the coffee producing regions in North Sumatra. The decline in coffee production in Samosir Regency indicates the need for a coffee farming development strategy so that the area can become one of the coffee production centers in the future. This study aims to determine the internal and external factors in the development of arabica coffee farming and to determine the development strategy of arabica coffee farming in Ronggur Nihuta District, Samosir Regency. The sampling technique in this study used the Purposive Sampling method through interviews with farmers in a Focus Group Discussion (FGD). The number of samples determined was 30 coffee farmers. The data analysis method was carried out descriptively through the SWOT method by looking at the internal and external factors of coffee farming then developing strategies by evaluating strengths (strenghs), weaknesses (weaknesses), opportunities (opportunities), and threats (threats). The results showed that the strengths of coffee farming development were the availability of land, availability of seeds, support for facilities and infrastructure, availability of capital and experience in coffee farming. Opportunities utilized are geographical conditions and location, coffee price stability, market availability, the role of farmer groups, and high coffee demand. Alternative strategies for the development of arabica coffee farming in Ronggur Nihuta Subdistrict are utilizing the land area as optimally as possible followed by increasing knowledge of coffee maintenance, using superior seeds, utilizing technology to be able to increase production to meet market demand. So that the implication of the results of this study is to increase the income and welfare of coffee farmers. For this reason, the role of agricultural extension officers is needed in assisting farmers to introduce superior seeds, technology and information, the use of organic fertilizers, and the need to strengthen farmer groups and cooperative institutions to support farmers' capital.